Reciprocal interference between ants and stingless bees attending the honeydew-producing homopteran Aetalion reticulatum (Homoptera: Aetalionidae) - Almeida-Neto, Mário [UNESP]; Izzo, Thiago J. [UNESP]; Raimundo, Rafael L. G.; Rossa-Feres, Denise C. [UNESP] (My University, 2003)
We evaluated the reciprocal effects between foragers of the ants Camponotus crassus and of the stingless bees Trigona hyalinata on aggregations of the honeydew-producing treehopper Aetalion reticulatum. The interactions were observed in Bauhinia variegata (Caesalpiniaceae) and Mangifera indica (Anacardiaceae) trees. We recorded the presence/absence of each attendant species in homopteran aggregations to test if the observed co-occurrence is lower than that expected by chance. An exclusion experiment was performed in which each attendant species was excluded from aggregations in order to test if an attendant species is more likely to occupy aggregations where the other attendant is not present. We also recorded the number of individuals of each attendant species in homopteran aggregations to search for any correlation between homopteran and attendant abundances. Additionally, we performed experiments using termites (Termitidae, Isoptera) as models to verify if the attendant species have the potential to defend A. reticulatum against natural enemies. The co-occurrence of attendant species was lower than that expected by chance. Homopteran aggregations without stingless bees were more visited by ants than those in which T. hyalinata was present, and vice-versa. The abundance of stingless bees was proportional to homopteran abundance, while ants abundance was not correlated to homopteran abundance. Both attendant species attacked the natural enemies models when we glued the termites ca. 1 cm away from homopteran aggregations, but only ants removed termites glued 5-7 cm away from aggregations. We suggest that the effects of non-formicid attendants should be included as another factor influencing the costs and benefits of ant-homopteran interactions, since honeydew availability for ants also depends on the presence and behavior of interspecific attendants.
Keywords: Camponotus crassus; Defensive behavior; Mutualism; Territoriality; Trigona hyalinata; Trophobiosis; Aetalion; Aetalionidae; Anacardiaceae; Apoidea; Bauhinia; Bauhinia variegata; Caesalpinioideae; Camponotus; Formicidae; Hemiptera; Isoptera; Mangifera; Mangifera indica; Meliponinae; Termitidae; Trigona